2006
DOI: 10.1369/jhc.5a6778.2005
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Anti-albumin Antibodies Are Responsible for False Positivity in Diagnosis of Autoimmune Premature Ovarian Failure

Abstract: Autoimmunity is a well-established causative factor of premature ovarian failure (POF), and evidence for the same has been well reported in the literature. Detection of specific autoantibodies remains the most practical clinical research marker of any autoimmune disease. Variation in efficiency and specificity in the detection of ovarian autoantibodies has been reported. However, the frequency of false positivity and a solution to overcome this has not yet been reported. Herein, we report autoantibody to album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…This indicates that not all women respond uniformly to the treatment. The 66 kDa reactivity is the reaction of naturally occurring abundant auto-antibodies to albumin was commonly seen in all patients and controls (lane C) and as described earlier [13]. A 'no primary antibody control' showed no immunoreactivity (lane NC).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…This indicates that not all women respond uniformly to the treatment. The 66 kDa reactivity is the reaction of naturally occurring abundant auto-antibodies to albumin was commonly seen in all patients and controls (lane C) and as described earlier [13]. A 'no primary antibody control' showed no immunoreactivity (lane NC).…”
Section: Resultssupporting
confidence: 72%
“…Although various investigators have demonstrated that there is multiplicity of molecular and cellular targets in human ovarian autoimmunity, there is still a need to identify all specific ovarian targets [29,30]. However, from our earlier findings we have investigated the cause of the non-specificity and were able to demonstrate true molecular and histochemical targets [5,13]. Once the patient tests positive for AOA by Western blot analysis, the serum is screened by us to identity the cell types which are targeted, using IHC which employs a novel blocking recipe [13].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations